Staphylococcus aureus Panton‐Valentine Leukocidin triggers an alternative NETosis process targeting mitochondria. Issue 2 (25th November 2020) - Mazzoleni, Viola; Zimmermann, Kiran; Smirnova, Anna; Tarassov, Ivan; Prévost, Gilles
Abstract: Panton‐Valentine Leukocidin (PVL) is a bicomponent leukotoxin produced by 3%‐10% of clinical Staphylococcus aureus (SA) strains involved in the severity of hospital and community‐acquired infections. Although PVL was long known as a pore‐forming toxin, recent studies have challenged the formation of a pore at the plasma membrane, while its endocytosis and the exact mode of action remain to be defined. In vitro immunolabeling of human neutrophils shows that Neutrophil Extracellular Traps (NETosis) is triggered by the action of purified PVL, but not by Gamma hemolysin CB (HlgCB), a structurally similar SA leukotoxin. PVL causes the ejection of chromatin fibers (NETs) decorated with antibacterial peptides independently of the NADPH oxidase oxidative burst. Leukotoxin partially colocalizes with mitochondria and enhances the production of reactive oxygen species from these organelles, while showing an increased autophagy, which results unnecessary for NETs ejection. PVL NETosis is elicited through Ca 2+ ‐activated SK channels and Myeloperoxidase activity but is abolished by Allopurinol pretreatment of neutrophils. Moreover, massive citrullination of the histone H3 is performed by peptidyl arginine deiminases. Inhibition of this latter enzymes fails to abolish NET extrusion. Unexpectedly, PVL NETosis does not seem to involve Src kinases, which is the main kinase family activated downstream the binding of PVL F subunit to CD45 receptor, while the specific kinase pathway differs from the NADPH oxidase‐dependent NETosis. PVL alone causes a different and specific form of NETosis that may rather represent a bacterial strategy conceived to disarm and disrupt the immune response, eventually allowing SA to spread.